Predictive value of direct bilirubin and total bile acid in lung adenocarcinoma patients treated with EGFR-TKIs - Yuting Li; Bicheng Wang; Shihong Fei; You Qin (BMC Pulmonary Medicine)
Abstract Epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) have been the standard treatment for patients with sensitizing EGFR mutation. However, almost all patients eventually acquire resistance to EGFR-TKIs. Therefore, easily available parameters to estimate the outcome of lung adenocarcinoma patients treated with EGFR-TKIs are in urgent need. Lung adenocarcinoma patients harbored EGFR sensitive mutant and received EGFR-TKIs as first-line or second-line treatment were recruited in the study. X-tile software were utilized to determine the optimal cut-off value of Alkaline phosphatase (ALP), direct bilirubin (DB), total bile acid (TBA), and high-density lipoprotein-cholesterol (HDL-C). The prognostic value of ALP, DB, TBA, and HDL-C for Progression-free survival (PFS) in patients were evaluated by the Kaplan-Meier curve. We applied univariate and multivariate survival analysis to identify the independent predictor for PFS in patients with EGFR-mutant advanced lung adenocarcinoma and received EGFR-TKIs. A total of 131 lung adenocarcinoma patients with a median age of 58 years old were included in the final analysis. Patients with elevated level of DB and HDL-C showed a longer PFS, while high level of ALP and TBA indicated shorter PFS in response to EGFR-TKI treatment. The multivariate survival analyses revealed a significant association of prolonged PFS with increased DB, and decreased TBA. In conclusion, these findings suggest that DB and TBA were significant independent predictors of PFS in EGFR-TKI-treated patients with advanced lung adenocarcinoma.